(untitled) (Olhar de Professor, 2023)
This article, resulting from a master’s research, aimed to identify, from the perspective of ten graduate teachers with teaching experience between 7 and 15 years, all with undergraduate and postgraduate degrees in technical areas and effective ties to a public university in Minas Gerais, how their professional teaching identity is constituted. Data obtained from semi-structured interviews were analyzed to identify their teaching knowledge and practices, using Maurice Tardif’s theoretical framework, and to address the objectives proposed in this study. According to the research participants, the knowledge acquired from their undergraduate programs does not encompass all the complexity involved in the knowledge necessary for teaching. They acknowledge the need for aptitude to construct new knowledge and reframe existing knowledge in their pedagogical practice, demonstrating the imperative for Higher Education Institutions to promote actions aimed at qualifying and professionally developing these teachers.